2017
DOI: 10.1080/10717544.2016.1267822
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of sericin-based conjugates by click chemistry: enhancement of sunitinib bioavailability and cell membrane permeation

Abstract: Sericin is a natural protein that has been used in biomedical and pharmaceutical fields as raw material for polypeptide-based drug delivery systems (DDSs). In this paper, it has been employed as pharmaceutical biopolymer for the production of sunitinib-polypeptide conjugate. The synthesis has been carried out by simple click reaction in water, using the redox couple L-ascorbic acid/hydrogen peroxide as a free radical grafting initiator. The bioconjugate molecular weight (50 kDa5Mw5 75 kDa) was obtained by SDS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…CSMs have the ability to sequester chemotherapeutic agents and release them in a controlled pattern, and thus maintain a sustained high concentration of chemotherapeutics drugs in tumor tissue. 10,14,15 It is also debatable whether DEB-TACE presents with superior survival benefits compared with cTACE in HCC patients. A previous study displayed comparable OS between DEB-TACE with DC Bead ® and cTACE in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…CSMs have the ability to sequester chemotherapeutic agents and release them in a controlled pattern, and thus maintain a sustained high concentration of chemotherapeutics drugs in tumor tissue. 10,14,15 It is also debatable whether DEB-TACE presents with superior survival benefits compared with cTACE in HCC patients. A previous study displayed comparable OS between DEB-TACE with DC Bead ® and cTACE in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Nature is an incredible source of drugs [28][29][30], including interesting bioactive anticancer molecules, even though they sometimes exhibit bioavailability issues that can be overcome by the use of proper vehicles or chemical modifications [31][32][33]. Concerning this, Do et al [34] reported the anticancer properties of 1-(5,7-dimetoxy-2,2dimetyl-2Hcromen-8-yl)-but-2-en-1-on (malloapelta B, malB), isolated from Mallotus apelta, which is able to inhibit the activation of nuclear factor kappa B (NF-kB) and is responsible for downregulating pivotal genes involved in inflammation.…”
Section: Contributionsmentioning
confidence: 99%
“…In another study, SUT was encapsulated in alginate nanoparticles using calcium chloride as a crosslinker [18], while Alshetaili et al developed three different formulations for SUT delivery to colon cancer cells by the nanoprecipitation technique using various concentrations of poly-lactic-co-glycolic acid (PLGA) and pluronic acid as surfactant [19]. Another interesting strategy involved the synthesis of a sunitinib-sericin conjugate by simple click reaction in water using L-ascorbic acid/hydrogen peroxide as a free radical grafting initiator [20]. On the contrary, only two works report on SUT imprinted polymers [4,5].…”
Section: Introductionmentioning
confidence: 99%